(untitled) (American Journal of Multidisciplinary Research and Innovation, 2023)
The study examines the effects of disablers on pupils’ academic performance in linear programming at Zambia’s Nkeyema secondary school. The study applied interpretivist views and was entirely qualitative. The lived experiences of fifteen (15) participants which included 8 girls and 7 boys were also extracted using a homogenous (purposive) sample technique. These were previous Nkeyema secondary school pupils who had completed grade twelve. In-depth interviews and group discussions produced the data, which was then thematically analysed. The findings of this research showed that a number of disablers affected how well pupils performed academically in linear programming. One of them was the travel time required for pupils, as well as the lack of quality teaching and learning tools like textbooks. Furthermore, inefficient teaching methods employed by some teachers, lack of parental support, and pupils’ lack of prior knowledge negatively affected performance in linear programming final examinations. In an effort to address the issues with teaching linear programming in grade twelve, the following suggestions were made: The Ministry of Education should build schools close to neighborhoods to minimise the distance that pupils must travel and also lower absenteeism. In order to ensure that pupils are learning properly, it should also make sure that universities and other educational institutions incorporate linear programming while training new teachers. Also, schools should receive enough funding to purchase instructional materials. Teachers should use learner-centered activities and 21st-century teaching techniques to impart the subject. To encourage pupils to attend class and learn, the government should build more boarding schools and school administration should arrange them meals. The study concluded that pupils in grade twelve performed poorly in linear programming. The lecture method of instruction and the prevalence of disablers in its delivery all led to the pupils’ subpar academic achievement.